Lassie Come Home - Eric Knight (London, United Kingdom Penguin Books Ltd, 1994)
When Sam Carraclough fall on hard times, he is forced to sell his prize collie to a wealthy family. But Lassie, although she is taken hundreds of miles away, knows it is her duty to meet young Joe from school - so she starts on the long and difficult journey home.
Keywords: Action -- Action; Adventure -- Adventure